Real economy and financial market. Long and short-termvolatility determinants in sub-Saharan economies - Kliber, Agata; Świerczyńska, Katarzyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
This paper presents analyses of the fictitious forces which are appearing where theframe of reference is moving simultaneously on the linear and rotational path. Finally, it givesa concept of the construction of a power plant. The power plant used the energy which derivedfrom the rotation of the Earth.
Mathematical Economics; 2017; Nr 13 (20); s. 37-58
Keywords: complex number; derivative; Coriolis acceleration; Coriolis force; Coriolispower plant